Financing sustainable development: Shall we throw more money at the problem or start with doing better with existing resources? - Vos, Rob (Erasmus School of Social and Behavioural Sciences, 2023)
Reforming development assistance and debt relief have been main threads in Geske Dijkstra’s notable professional career. We worked together on those issues over two decades ago while we were both at the International Institute of Social Studies (ISS). Plus ça change? Since the outbreak of the COVID-19 pandemic lowincome countries have been hit hard economically; first by the global recession induced by the public health related lockdowns, then by spikes in food, fuel and fertilizer prices associated with the recovery from the recession and pandemicrelated supply disruptions, and subsequently by further surges in food and fertilizer prices with the outbreak of the war in Ukraine. The capacity of poor nations’ governments to protect the livelihoods of their populations from the impacts of the multiple crises quickly eroded. Bilateral development assistance failed to come to a rescue, multilateral contingency financing mechanisms proved inadequate and fraught with old-fashioned, ill-conceived policy conditionality, and the lack of proper sovereign debt work-out mechanisms was painfully felt again as the number of low-income countries facing severe debt distress doubled during these years of crisis. Proper reforms on all these dimensions remain an unfinished agenda. In addition, yet another looming global crisis – climate change – is calling for transformative investments in production systems to stave off this existentialist threat and to set economies on sustainable development pathways. The calls for transformative change come with massive needs for additional (development) finance in magnitudes of hundreds of billions, if not trillions, of US dollars per year over the next couple of decades. However, the prospects for mobilizing new funding in such magnitude seem elusive if only considering the experience with creating new facilities for climate finance.